Practical Tools for Youth Entrepreneurs An Applied Approach for South Africa and Beyond - van der Westhuizen, Thea.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
This open access book inspires young entrepreneurs to embark on the journey toward the future of work through actionable entrepreneurship, especially focusing on South Africa. Its insights and tools extend beyond borders, suiting the Global South and emerging markets. Using systemic action learning, the author guides readers in developing both internal and external aspects of youth entrepreneurship. Part One delves into the internal facets, exploring the interaction of entrepreneurial Heartset, Mindset & Handset that shape entrepreneurial behavior. The terms 'entrepreneurial heartset,' 'mindset,' and 'handset' encompass the neurological, thought-related, and behavioral dimensions of entrepreneurship $1 (Bthe Triple H. The book illustrates external aspects through the SHAPE model (Shifting Hope Activating Potential Entrepreneurship) and YES network (Youth Entrepreneur Support). These models offer an ecosystem strategy for young entrepreneurs. Part Two equips aspiring youth entrepreneurs with tools to overcome creativity barriers, generate business ideas, and nurture entrepreneurial traits. The SHAPE Four Quadrant Business Model Canvas and dropshipping for start-ups are among the implementable tools presented. The book introduces original models for youth entrepreneur internal and external domains, offering substantive insights. The SHAPE Lab delivers comprehensive toolkits for youth entrepreneurship development. Professor Thea van der Westhuizen (PhD) is an entrepreneur and academic at the University of KwaZulu-Natal, and the founder of SHAPE. Recognized at The Innovative Youth Incubator Awards, she advocates for sustainability and youth empowerment. With a rich history of impactful collaborations, she's a driving force in entrepreneurship.s
Part I: Connecting Systems -- Chapter 1: Introduction to Youth Entrepreneurship -- Chapter 2: Internal Domains Entrepreneurial Heartset, Mindset and Handset -- Chapter 3: Youth entrepreneur ecosystem -- Part II: The SHAPE Lab: Tools for Enabling Youth Entrepreneurship -- Chapter 4: Tools to shift hope and activate potential entrepreneurship -- Chapter 5: Enabling tools for entrepreneurship in South Africa -- Chapter 6: Tools to assist in making the move into entrepreneurship -- Chapter 7: New customers and product development -- Chapter 8: Tools to develop core business, growth and sustainability -- Part III: Journaling of the Author on Working as a Youth Entrepreneur -- Chapter 9: En route: A self-reflective lens as a case study.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Entrepreneurship; New business enterprises; Entrepreneurship